Binding proteins enhance specific uptake rate by increasing the substrate–transporter encounter rate. (24th April 2015) - Bosdriesz, Evert; Magnúsdóttir, Stefanía; Bruggeman, Frank J.; Teusink, Bas; Molenaar, Douwe
<x xml:space="preserve">Abstract</x> Microorganisms rely on binding‐protein assisted, active transport systems to scavenge for scarce nutrients. Several advantages of using binding proteins in such uptake systems have been proposed. However, a systematic, rigorous and quantitative analysis of the function of binding proteins is lacking. By combining knowledge of selection pressure and physiochemical constraints, we derive kinetic, thermodynamic, and stoichiometric properties of binding‐protein dependent transport systems that enable a maximal import activity per amount of transporter. Under the hypothesis that this maximal specific activity of the transport complex is the selection objective, binding protein concentrations should exceed the concentration of both the scarce nutrient and the transporter. This increases the encounter rate of transporter with loaded binding protein at low substrate concentrations, thereby enhancing the affinity and specific uptake rate. These predictions are experimentally testable, and a number of observations confirm them.